POSSIBILITIES OF ULTRASONIC DIAGNOSTICS OF DIABETIC PHETOPATHY WITH GESTATIONAL DIABETES MELLITUS - Ольга Владимировна Рожкова; Иван Григорьевич Брусенцов (The Publishing House Medicine and Enlightenment, 2020)
The aim of the research - determination of the informativity of echographic markers of diabetic fetopathy: macrosomia, hepatomegaly, cardiomegaly/cardiopathy, edema and thickening of the subcutaneous fat layer, double-contour of the fetal head, polyhydramnios with an assessment of sensitivity and specificity, as well as their combination. Materials and methods. A retrospective comparative study of ultrasound data conducted 3-7 days before delivery was performed in 122 patients with full-term single-fetus pregnancy with diagnosed GSD. The information content of ultrasound markers of diabetic fetopathy was evaluated in accordance with the postnatal diagnosis in a newborn. 2 groups of subjects were formed depending on the postnatal diagnosis: the first group (n = 15) - newborns were postnatally diagnosed with DF, the second group (n = 107) - newborns without diabetic fetopathy. Results. The ultrasound markers of diabetic fetopathy in the clinical recommendations for gestational diabetes have high sensitivity and specificity, but the prognostic value of a positive result does not exceed 50 %. Diagnosis of cardiopathy/cardiomegaly in full-term pregnancy is associated with emerging technical difficulties, has limited opportunities to diagnose the pathological condition. Conclusion. The combination of four or more ultrasound markers increases the probability of post-Natal confirmation of diabetic fetopathy with sensitivity 90.9 %, specificity - 93.8 %.